Experiences of the Pandemic in a Village in the Peruvian Andes: Responses and Community Resilience Tactics in a Rural Community - Arenas Sotelo, Eric (2025)
This article presents the results of an ethnographic study on the COVID-19 health crisis in a rural community in the province of Paucartambo (Cusco) and the contributions of this case to understand the community character of resilience. This research was conducted in early 2022 (March to May) collecting, through interviews and talking maps, the experiences that members and authorities of the community had on the management of the pandemic from March of 2020 to May of 2022. From this, five tactics of community resilience were identified, organized in two dimensions: the first refers to the transformations and adaptations of forms of governance for community management, while the second deals with the interconnection and construction of family and social networks in the community. In a conclusive and transversal manner, we reflect on the community dimension of resilience. Finally, the main public policy contributions of the research are presented.